Unraveling the potential of selected South African indigenous plants as biocontrol agents against aflatoxin-producing Aspergillus species - Kritzinger, Quenton (University of Pretoria, 2024)
Dissertation (MSc (Medicinal Plant Science))--University of Pretoria, 2019.